PERAN PENGENDALIAN INTERNAL DAN WHISTLEBLOWING SYSTEM DALAM MEMPERKUAT PENCEGAHAN KECURANGAN STUDI PADA PT TUMBAKMAS NIAGASAKTI REGIONAL JAWA BARAT - Fajar Noviardiansyah; Rachmat Agus Santoso (Journal Economic Management and Business, 2026)
Fraud within organizations poses a significant risk that may disrupt operational stability, reduce trust, and hinder the achievement of organizational objectives. Therefore, companies require effective control mechanisms to minimize potential misconduct. This study aims to analyze the role of internal control and whistleblowing systems in strengthening fraud prevention at PT Tumbakmas Niagasakti Regional West Java. A quantitative approach was employed using a survey method through questionnaires distributed to 132 employees as respondents. Data were analyzed using multiple linear regression with SPSS software. The findings indicate that internal control and whistleblowing systems contribute positively to fraud prevention, both partially and simultaneously. Effective internal control enhances supervision and compliance with procedures, while whistleblowing systems promote transparency and support early detection of unethical practices. The study highlights the importance of integrating control systems and reporting mechanisms to establish more accountable governance and strengthen organizational fraud prevention strategies.